(untitled) (Tribhuvan University Journal of Microbiology, 2024)
Objectives: To detect antibiotic resistance genes (ARG) genes and bacteria from surface water in Kathmandu. Methods: Bacteria were isolated on MacConkey agar and Eosin Methylene Blue (EMB) agar, further identified by biochemical test. Antibiotic susceptibility tests, and ESBL production was detected following CLSI guidelines. Plasmid was extracted by phenol and chloroform method and blaTEM, blaSHV, blaCTX-M, blaNDM-1 and blaOXA-48 genes were amplified by PCR. Results: Out of 100 isolates of Escherichia coli (60) and Klebsiella spp (40), 15 strains were ESBL producers. Of isolated ESBL positive isolates, total isolated strains were sensitive to imipenem and ofloxacin, whereas, from 85 non ESBL producers, all strains were sensitive to imipenem, ofloxacin, cefotaxime, ceftazidime, and ceftriaxone. The most prevalent gene distributed in surface water includes blaTEM, followed by blaNDM-1 and blaCTX-M genes. The combination of blaCTX-M and blaTEM (97.7%) was the most prevalent, followed by blaSHV and blaTEM (5.4%) genes. Conclusion: The detection of ESBL positive genes and bacteria in surface water indicates the growing challenge of antibiotic resistance. It requires a comprehensive response involving environmental management, public health strategies, policy changes, and global cooperation.